PENGARUH MODEL PROBLEM BASED LEARNING DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI KELAS XI IPA MAN 2 MODEL PALU - Herlina, Herlina (JSTT, 2016)
This study was aimed to: (1) investigate the influence of Problem Based Learning model toward students’ learning achievement; (2) examine the difference of students with high achievement motivation and those with low achievement motivation’s learning result; (3) test the interaction between Problem Based Learning model and achievement motivation toward students’ learning result on Biology subject of XI Grade Science Program at MAN 2 Model Palu. The method applied in this study was quasi-experiment. The population of this study was the XI Grade students of Science Program at MAN 2 Model Palu, comprised of 4 classes. Sample selection was determined through the assigment of random sampling technique. The independent variablse of this study were: the Problem Based Learning and Direct Instruction.The students’ learning result as the dependent variable, and the achievement motivation which served as the moderator variable. The data collected through learning achievement test and achievement motivation questionnaire. The data of the study were analyzed by two-way ANNOVA technique asssisted by the SPSS program version 16. The result of this study proved that: (1) the Problem Based Learning model had a significant influence on students’ learning result. It proved to be grander than the Direct Instruction in influencing students’ learning result; (2) there was a significant difference of students’ learning result between students who have high achievement motivation and those who have low achievement motivation. Students with high achievement motivation performed better result in their learning rather than the students with low achievement motivation; and (3) there was no presence of interaction between Problem Based Learning model and achievement motivation towards students’ learning result. Where the learningmodels (PBL and Direct Instruction) and the achievement motivation did not influence students’ learning result either at high or low level of achievement motivation.